The Influence of Geological Structure against Gunung Batu Pek in New Ritan Village, Tabang District, Kutai Kartanegara Regency - Al Chasani, Nur Rahman (Teknik Geologi Fakultas Teknik Universitas Mulawarman, 2025)
“Intrusi Atan” is one of the formations that compose the upper part of the Kutai Basin, dating from the Oligocene–Miocene. A notable feature of this Intrusion is Gunung Batu Pek, located in Ritan Baru Village. The aim of this study is to determine the characteristics of the rock at Gunung Batu Pek as well as its genesis. The research was conducted using the FFD (Fault–Fracture–Density) method to identify the structural geological trends controlling the area, followed by geological mapping to characterize the local rock types. The study identified six stations, each revealing that Gunung Batu Pek is composed of andesite, exhibiting well-developed columnar jointing. The Atan Intrusion formed due to volcanic activity associated with an extensional phase of the Kutai Basin during the Late Oligocene to Early Miocene.